Hypoglycemia and Medical Expenses in Patients with Type 2 Diabetes Mellitus: An Analysis Based on the Korea National Diabetes Program Cohort. - Sang Youl Rhee (PLoS ONE, 2016)
BACKGROUND AND AIMS:Hypoglycemia is one of the most important adverse events in individuals with type 2 diabetes mellitus (T2DM). However, hypoglycemia-related events are usually overlooked and have been documented less in clinical practice. MATERIALS AND METHODS:We evaluated the incidence, clinical characteristics, and medical expenses of hypoglycemia related events in T2DM patients based on the Korea National Diabetes Program (KNDP), which is the largest multi-center, prospective cohort in Korea (n = 4,350). For accurate outcomes, the KNDP data were merged with claims data from the Health Insurance Review and Assessment Service (HIRA) of Korea. RESULTS:During a median follow-up period of 3.23 years (95% CI: 3.14, 3.19), 88 subjects (2.02%) were newly diagnosed with hypoglycemia, and the incidence of hypoglycemia was 6.44 cases per 1,000 person-years (PY). Individuals with hypoglycemia were significantly older (59.7±10.7 vs. 53.3±10.4 years, p < 0.001), had more hospital visits (121.94±126.88 days/PY, p < 0.001), had a longer hospital stays (16.13±29.21 days/PY, p < 0.001), and incurred greater medical costs ($2,447.56±4,056.38 vs. $1,336.37±3,403.39 /PY, p < 0.001) than subjects without hypoglycemia. CONCLUSION:Hypoglycemia-related events were infrequently identified among the medical records of T2DM subjects. However, they were associated significantly with poor clinical outcomes, and thus, hypoglycemia could have a substantial burden on the Korean national healthcare system.